Post Covid-19 Assessment of Strengths and Weaknesses of Urban & Rural Areas of Different Countries - Saleem, Hamza; Nadeem, Alishba; Waheed, Fatima; Waseem, Fariha; khan, Aisha (Riviera Publishing, 2023)
Introduction: This study aims to assess the vulnerability of multidimensional pandemics/public health (physical, social, economic & attitudinal) from rural and urban togetherness after COVID-19 and to suggest appropriate coping strategies/mechanisms for effective pandemic risk reduction. Method: This study is qualitative and discusses the Post COVID-19 assessment of the strengths and weaknesses of urban and rural areas in different countries to understand the way out for Pakistan. Result: Planners can make use of the chances that the pandemic has presented. It should be emphasized once more that this crisis shows how critical analyses of the significance of cities and their governance are necessary. Now that they are aware of the significant implications of the pandemic on cities, it is believed that planners and local authorities will be more successful in mobilizing support for transformative initiatives toward dealing with other significant concerns, such as climate change, that are hanging over citie. Conclusion: The COVID-19 pandemic has caused significant disruptions in daily life across cities worldwide. Researchers have studied its impact on urban sectors to better anticipate and respond to future crises. While effects and response strategies vary across different locations, lessons learned can inform better preparedness for future crises. The pandemic is expected to bring profound changes in how cities are run and governed, presenting opportunities for transformative initiatives towards a more environmentally friendly future. Critical analyses of cities and their governance are necessary to address significant concerns such as climate change.